(untitled) (Research, Society and Development, 2021)
Diabetes Mellitus (DM) is a serious public health problem that lacks new therapeutic alternatives, among which, phytotherapy stands out. This study aimed to evaluate the activity of hydroethanolic extract of leaves and flour from Guabiju fruits (Myrcianthes pungens) on the laboratory parameters of diabetic animals. The flour of the Guabiju fruits incorporated into the daily diet in the form of pelleted feed or the extract of the Guabiju leaves administered by gavage (oral dose of 300 mg/kg/day), were administered in an experimental model of Wistar rats with type 1 DM induced by alloxane, for 45 and 90 days, respectively. The anti-hyperglycemic effect and other biochemical parameters were evaluated, such as triglycerides, total cholesterol, and liver (AST) and renal (creatinine) function marker enzymes. The outcome of both treatments did not result in a marked decrease in fasting glycemia, improvement of the lipid profile or renal function when compared to untreated diabetic rats. However, treatment with Guabiju leaf extract prevented the increase in liver injury, and the results of the hepatic function showed significant beneficial changes in animals treated with Guabiju leaf extract, with decreased levels of AST. The AST value for non-diabetic rats was 72.12 ± 10.52 mg/dl, for diabetic rats it was 111.0 ± 16.84 mg/dl and for treated diabetic rats it was 82.66 ± 5.50 mg/dl (p < 0.05). This action in preventing typical complications of DM, such as liver damage, in a low dose, demonstrates that this plant can present a possible therapeutic activity, which must be refined with further tests and clinical trials that prove its effectiveness and safety.